Concomitant LATE‐NC in Alzheimer's disease is not associated with increased tau or amyloid‐β pathological burden. (22nd September 2020) - McAleese, K. E.; Walker, L.; Erskine, D.; Johnson, M.; Koss, D.; Thomas, A. J.; Attems, J.
Abstract : Aims: Limbic‐predominant age‐related TDP‐43 encephalopathy neuropathological change (LATE‐NC) is present in approximately 50% of Alzheimer's disease (AD) cases and is associated with accelerated cognitive decline. Studies indicate a potential synergistic relationship between LATE‐NC and hyperphosphorylated tau. It is unknown if LATE‐NC is an independent driver of cognitive impairment or exerts its influence through synergistic relationships with tau. This cliniconeuropathological study investigated the impact of LATE‐NC on quantified measures of AD‐associated pathology and its impact on clinical measures. Methods: A total of 61 AD cases underwent neuropathological assessment for LATE‐NC and quantitative assessment [area covered by immunoreactivity (IR)] for early conformational tau (MC‐1), late‐stage hyperphosphorylated tau (AT8) and amyloid‐β in the amygdala and five neocortical regions. Clinical measures included age of disease onset, final Mini‐Mental State Examination (MMSE) score and rate of cognitive decline. Results: LATE‐NC was present in 41 AD cases (AD/LATE‐NC; 67.2%). No significant differences in MC‐1‐IR, AT8‐IR or 4G8‐IR were observed in any region between AD/LATE‐NC and AD without LATE‐NC, indicating no accelerated aggregation or hyperphosphorylation of tau proteins in the AD/LATE‐NC cases. Final MMSE was significantly lower in AD/LATE‐NC cases and was significantly associated with LATE‐NC score even when controlled for the presence of both MC‐1‐IR and AT8‐IR ( P = 0.009). Conclusion: The presence of LATE‐NC in AD is not associated with an increase in the burden of early or late tau or Aβ pathology. LATE‐NC is associated with a lower final MMSE score independent of tau pathology. Abstract : The presence of Limbic‐predominant age‐related TDP‐43 encephalopathy neuropathological change (LATE‐NC) is not associated with an increase in the burden of early or late tau or Aβ pathology in Alzheimer's disease. LATE‐NC is associated with a lower final MMSE score independent of tau pathology.